Holding accountants accountable : how professional standards can lead to personal liability - Matthews, Jeffrey G., 1973- (Wiley corporate F & A series., 2020)
"The author details his incredible journey as a forensic accountant and how he faced death threats, retaliation and family hardships during various fraud investigations. He was tested on numerous occasions but never deviated from professional standards. Over the years, he has collected countless stories representative of the common tendencies that hinder practitioner's ability to detect, deter, and prevent fraud and misconduct, many of which could violate professional standards. In this book he details FRAUD and how accountants can avoid being caught in unethical practices: F -- Forgetting the Present: Many practitioners feel it could never happen to them or to their clients. However, one needs only to grab today's newspaper to address this fallacy. Professionals must stay on top of emerging trends to identify new areas of weakness, or they could find themselves on the front page. R - Relying on Others: Oftentimes, practitioners face time and budget constraints, which require delegation to lower level staff. A work environment that is not conducive to collaboration, relies on inexperienced staff, and combined with an over-extended supervisor with limited time (or budget) can lead to a disaster A -- Accepting Not Testing: Practitioners must maintain a healthy dose of skepticism in discharging their duties. Having a habit of Accepting not Testing can put an examiner in a crosshairs of agencies that will certainly do more than just test. U- Underestimating the Effort and Qualifications: Many practitioners are presented with assignments that have little time, budget or direction. Sometimes, practitioners fight to "win" those very assignments and shortcuts to the finish can ensue. Another iteration is within Firms espousing an "eat what you kill" environment which can push examiners to accept engagements they are not fully qualified to perform. D -- Determining the Outcome Prior to Performing the Assignment. Accountants have all heard this hundreds of times; "This is a relationship business." But they have also heard horror stories that begin with "Well, I knew this guy...." Or "I had these friends and....." This is another area ripe for abuse, in that examiners can become close to their clients and establish biases. Sometimes, the examiner may not realize there is a bias at all. Overlooking a situation, in while looking forward to the holiday party invite or the honey baked ham gift basket can lead an examiner to look for a new career"--